The physiology of the tick Rhipicephalus Appendiculatus in relation to the transmission of Theileria Parva. - Sebitosi, E.N.K. (Ahmadu Bello University, 1998)
The factors within the tick vector R. appendiculatus that influence the development and transmission of the parasite Theileria parva were investigated and found to include the blood meal, phenoloxidase, enzymes, hormones and lectins. The cattle blood meal, when fractionated into cells and plasma components by centrifugation and provided to ticks in vitro, indicated that plasma alone negated the development and infectivity of T. parva to bovine lymphocytes leading to only 0.07% infections of T. parva in the peripheral blood lymphocytes, cells showed 1.02% , whole blood revealed 20% while the ticks fed in vivo on rabbits produced the highest infection (67.9%). For the first time in vitro infections of lymphocytes was carried out by sporozites obtained from ticks fed in vitro. Lectins were detected in the haemolymph, gut and salivary glands from partially fed female adult R. appendiculatus and R. pulchellus. The gut lectins were agglutinated by several vertebrate erythrocytes, the highest being rabbit with a titre of 4096. No agglutination was observed when common domestic cattle, goat and sheep cells were used. The gut lectin was inhibited by fetuin, D(+) galactosamine and D(-) manosamine while the haemolymph lectin was inhibited best by xylose, N-acetyl galactosamine and B-D-fructose. The role of lectins investigated by feeding the carbohydrates and glycoproteins that inhibited agglutination to ticks in vitro, to ticks together with infected blood, revealed reduced or no infections in the salivary glands. Ticks fed upon immunised rabbits immunised with the lectins had also reduced infection rates (50%) compared to control (80%) which implied that these lectins were involved in the control of the development of T. parva. Anti-sera to lectins raised by immunising rabbit and mice with red blood cells to which an immunogen had been adsorbed reacted with purified piroplasms and bound the shizont stages of this parasite opening a new avenue in the possible intervention of Theileriosis at the piroplasm stage and underscoring the role of lectins in the development of this parasite. The digestive gut cells and lining and salivary viii gland type III acini from the ticks fed upon these immunized rabbits were damaged an indication that the antibody traversed the gut, reaching target organs and remained functionally active. Subjection of these lectins to enzyme treatments before agglutination assays revealed the lectins to be proteins, most likely glycoprotein in nature. The haemolymph was thermo-labile above 40 C, affected by freezing and thawing treatments shown by the reduction in agglutination properties, while the gut lectin was thermal stable, and withstood temperatures up to 80 °C. Optimum haemagglutination depended upon neutral pH conditions and the agglutination activity was C 2+/ Mg2+ dependent. Among the hormone effects on ticks, topical application of ecdyson on ticks significantly reduced the moulting time as well as the engorgement weights. In vitro feeding of 20 hydroxyecdyson and juvenile hormones resulted into various responses among which was the significant reduction of engorgement weights of nymphs, moulting time and infection rates. The deleterious effects of hormones on ticks should be further investigated. Enzymes particularly trypsin and protease were detected in the guts and not in the salivary glands using casein gel as substrate and results showed that there were higher levels in the infected females. These enzymes were blood meal induced and peaked at least 48 hr following a blood meal. The phenoloxidase system in Rappendiculatus, activated by methanol, indicated significantly low levels of phenoloxidase in the haemolymph, compared to insects (locusts) and Amblyoma variegatum. At least 95% of the phenoloxidase activity occurred in the plasma and was highest among the infected ticks indicating that infection with T. parva altered the normal levels if this enzyme activity and suggesting that the system may be involved in the "self" and "non self" recognition among ticks. Scanning electron microscopy revealed that the salivary glands had a "grape like" appearance with type I and II acini having smooth surfaces unlike the type III which were bigger and had sculptures. The infected type III acini were bigger and had diffuse surface structures. The type III acini had distinguished morphological features which did not exist in the other cells implying that the possible mechanism of entry of kinetes into the e cells was most likely specific receptors at the site of entry into these cells, coupled with chemical attraction as revealed by the glycogen deposits and was unlikely to be by chance as earlier suggested. The investigations revealed the lectins should be looked at as possible immunogens in the blocking of transmission of T. parva as well as anti- tick interventions in the future of theileriosis control.